1999
DOI: 10.1021/jm980657j
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity Relationships of Bisphosphate Nucleotide Derivatives as P2Y1 Receptor Antagonists and Partial Agonists

Abstract: The P2Y1 receptor is present in the heart, in skeletal and various smooth muscles, and in platelets, where its activation is linked to aggregation. Adenosine 3',5'- and 2',5'-bisphosphates have been identified as selective antagonists at the P2Y1 receptor (Boyer et al. Mol. Pharmacol. 1996, 50, 1323-1329) and have been modified structurally to increase receptor affinity (Camaioni et al. J. Med. Chem. 1998, 41, 183-190). We have extended the structure-activity relationships to a new series of deoxyadenosine bis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 60 publications
(100 citation statements)
references
References 38 publications
3
94
3
Order By: Relevance
“…5) that are blocked by the selective P2Y 1 antagonist MRS 2179 [19,104,105]. Interestingly, a single-stimulus-evoked EPSP with a time course between that of a fast and a slow EPSP (an intermediate EPSP) was shown to be blocked by PPADS, suramin, and the selective P2Y 1 receptor antagonist MRS 2179 [19].…”
Section: Slow Synaptic Transmissionmentioning
confidence: 99%
“…5) that are blocked by the selective P2Y 1 antagonist MRS 2179 [19,104,105]. Interestingly, a single-stimulus-evoked EPSP with a time course between that of a fast and a slow EPSP (an intermediate EPSP) was shown to be blocked by PPADS, suramin, and the selective P2Y 1 receptor antagonist MRS 2179 [19].…”
Section: Slow Synaptic Transmissionmentioning
confidence: 99%
“…Antagonism was defined as the ability to reverse completely the stimulation of PLC elicted by 30 nM 2-methylthioadenosine-5′-diphosphate, an agonist of nanomolar potency. In some cases the related nucleotides could be interconverted between agonists (or partial agonists) and antagonists with small structural changes [17][18][19]. SAR analysis indicated that the 2-position accommodated Cl or thioethers, while the N 6 -position was limited to Me or Et.…”
Section: Ribose-modified Nucleotide Analoguesmentioning
confidence: 99%
“…Methods utilized in these recent investigations include: conformationally constraining the ribose, or ribose-like, moiety of nucleosides and nucleotides to freeze a conformation that may provide favorable affinity and/or selectivity at P1 and P2 receptors [3,4]; modifying known receptor antagonists [5][6][7]; use of a template approach based on the pyridine family for the design of novel adenosine antagonists [8]; and the screening of chemical libraries in conjunction with molecular modeling [9].…”
Section: Introductionmentioning
confidence: 99%
“…Exploration of selective agonists and antagonists modulators is most advanced at the P2Y 1 and P2Y 12 receptors, but at most of the P2Y receptors selective pharmacological probes are lacking. [22][23][24][25][26][27][28][29][30][31][32] Compound 20 was shown to antagonize signaling of the P2Y 1 receptor selectively and with moderate potency. At the P2Y 1 receptor, the previously described high affinity antagonists are nucleotide derivatives and therefore highly charged, which is highly limiting in pharmacological studies due to low bioavailability and stability.…”
Section: Discussionmentioning
confidence: 99%
“…For example, antagonists of the P2Y 1 and P2Y 12 receptors are of interest as antithrombotic agents. [22][23][24][25][26][27][28][29][30][31][32] Agonists of the P2Y 2 receptor are of interest in the treatment of pulmonary diseases, including cystic fibrosis. The P2Y 6 receptor has recently been implicated in protection against apoptosis induced by TNFα.…”
Section: Introductionmentioning
confidence: 99%